La critique de l’épistémologie classique et ses implications pédagogiques chez John Dewey et Karl Popper - Alain Firode (Recherches en Éducation)
Dewey and Popper have both criticized classical theories of knowledge by opposing them with a naturalistic and evolutionary epistemology in which knowledge is thought to be an extension of vital activity. Although they aim at the same target, the two philosophers do not criticize classical epistemology for the same reasons. The error of most philosophers, for Dewey, is to have accepted "the spectator theory of knowledge" which identifies knowledge with an adequate representation of the reality ; according to Popper, it is to have remained prisoner of the "subjectivist epistemology" which limits knowledge to what is known by a subject. These two ways of looking at the fundamental error of Western philosophy result in two different criticisms of traditional pedagogy.